Pilot plant preparation of light-coloured protein isolates from de-oiled sunflower (Helianthus annuus L.) press cake by mild-acidic protein extraction and polyphenol adsorption. (February 2015) - Pickardt, Claudia; Eisner, Peter; Kammerer, Dietmar R.; Carle, Reinhold
Abstract: The aim of this study was to produce light-coloured protein isolates from sunflower press cake on a pilot plant scale. Mild-acidic extraction at pH 6 prevented discolouration due to co-extracted phenolic compounds and facilitated the adsorptive removal thereof using a styrene-divinylbenzene resin, coupled with ion exchange. To enhance protein solubility under acidic conditions, NaCl was added. Two concentrations (2 and 1.3 mol/L) were compared, previously identified as being most suitable for protein extraction and polyphenol adsorption. Protein isolates recovered by precipitation accumulated globular helianthinin, while highly soluble albumins were additionally recovered by ultrafiltration of the supernatants. Precipitated protein yields of 23–26% were obtained when 2 mol/L NaCl solution was used for extraction, whilst the lower salt level only gave protein yields of 15%. Albumin concentrates only marginally added to the overall yield with up to 5%. The physicochemical and functional properties of the precipitated proteins obtained at the different salt levels were comparable, being slightly inferior for the products obtained on a pilot plant compared to laboratory scale. Generally, protein isolates obtained by isoelectric precipitation were of high purity and light in colour, with protein contents of >94% and chlorogenic acid contents of <0.2%. Despite their poor solubility, they had fair emulsifying and excellent foaming properties. Altogether, sunflower protein isolates produced according to the novel process are promising food ingredients. The study demonstrated the feasibility of the process on a pilot plant scale. Moreover, the simultaneous recovery of phenolic compounds may enhance the economic viability of the overall process. Graphical abstract: Highlights: Protein isolates devoid of polyphenols were recovered from de-oiled sunflower cake. Mild-acidic extraction at high NaCl concentration improved protein yields. Adsorptive polyphenol removal was successfully applied at pilot-scale. Protein isolates from precipitation revealed bland colour and high protein content. Sunflower proteins are promising food ingredients as emulsifiers or whipping agents.